Poder e civilização no Brasil Imperial. A monarquia na perspectiva da história das ideias - Goncalves, Sérgio Campos (Diálogos Latinoamericanos, 2013)
Brazil ceased being a Portugal’s colony during the Nineteenth-Century. However, despite the Republic has been the dominant tendency in America, Brazil was the only country to adopt Monarchy when its political independency was reached. This essay deals with the concept of civilization as a monarchist power structure of the Brazilian State in the Nineteenth-Century. The objective is to point out that the ideia of civilization granted legitimacy to the monarchist system during the First Reign, the Regency and the Second Reign, acting as a determinant factor to maintain the regime.